The Use of Youtube based Learning Media to Attract Students' Self-regulated Learning Skills during Covid-19 Pandemic - Elsa Aula Islami (Universitas Negeri Manado, 2022)
In this pandemic situation, students are required to do online learning which makes students expected to have self-regulated learning skills so that they can catch the learning materials in school well. The purpose of this study are; 1). To find out the use of Youtube-based learning media in promoting students’ self-regulated learning skills during the pandemic, and 2). To find out the advantages and disadvantages of using Youtube-based learning media to promote students’ self-regulated learning skills during the pandemic, especially in 10th grade students of SMA Negeri 1 Pemalang. This research used descriptive qualitative as the research design. The research object is 10th grade students of SMA Negeri 1 Pemalang . The data collection in this study used abservation, questionnaire and interview. he result found that the use Youtube based learning media to attract students’ SRL skills during covid-19 pandemic are: students do SRL at home in order to improve their academic results, students used Youtube as learning media during pandemic, and Youtube videos makes it easier for students to understand material. Next, the result also found about the advantages of Youtube based learning media to promote students SRL skills during pandemic, those are: Youtube can be accessed anywhere and anytime, Youtube videos increase students motivation and interest to study, makes students happy and enjoy the learning material, has many explanatory videos related to the learning material, and students prefer to choose Youtube than textbooks. Last, the disadvantages are: the less interesting video and the monotonous videos makes students feel bored, an unstable internet connection makes it difficult to access Youtube, and an unstable internet connection makes the video resolution becomes low.